All pseudocapacitive MXene-MnO2 flexible asymmetric supercapacitor. (January 2022) - Wei, Yudi; Zheng, Mingming; Luo, Wenlong; Dai, Bo; Ren, Jiajia; Ma, Mingliang; Li, Tingxi; Ma, Yong
Highlights: Flexible asymmetric supercapacitor device based on MXene/CF as the negative electrode and MnO2 /CF as the positive electrode is successfully fabricated. The device exhibits specific capacitance of 20.5 F g −1 at 1.5 A g −1, voltage window of 1.5 V and energy density of 6.4 W h kg−1 at power density of 1107.7 W kg −1 . Two devices after bending 1000 times greater than 90° connected in series can easily power a 3.0 V LED for 90 min. Abstract: As a newly emerging 2D materials, MXene as electrode materials can be widely used in supercapacitors. However, symmetric supercapacitors based on MXene have a narrow voltage window due to oxidation occurs at a high anode potential. In this study, flexible asymmetric supercapacitor device is designed and fabricated by combining MXene/carbon fabric (CF) as the negative electrode and CF/MnO2 as the positive electrode in neutral electrolyte. The voltage window of the asymmetric device is successfully increased to 1.5 V, which is more than twice wider than that of the symmetric device. The maximum specific capacitance is 20.5 F g −1 at 1.5 A g −1 . The specific capacitance remains at 84% after 3000 charge-discharge cycles at 1.5 A g −1 . Furthermore, two asymmetric devices after bending 1000 times greater than 90° connected in series can easily power a 3 V LED for 90 min. The energy density of the asymmetric device is 6.4 W h kg −1 at 1107.7 W kg −1 power density. The work presented here shows that the asymmetric device based on MXene//MnO2 have excellent application prospects for the next generation of electrochemical energy storage devices.